The theatre of the self: poetic identity in the plays of Helene Cixous and Marina Tsvetaeva - Dobson, Julia (1996)
This comparative study of the theatre of Helene Cixous and Marina Tsvetaeva proposes a reading of their plays as a coherent corpus engaged specifically with the representation of poetic identity. Tsvetaeva's and Cixous' plays present a diverse range of characters who can be identified as poet-selves and who struggle to assert their identity in hostile environments. An inherent link is established between the thematic and the generic. Cixous' and Tsvetaeva's adoption of the theatre as genre in which to develop their conceptualisations of poetic identity is shown to be important to the thematic contexts in which the poet-selves are constructed. This study defines four elements: language, exile, sexual difference and Greek mythology, which are shown to be common to the representation of poetic identity in Tsvetaeva's and Cixous' plays. Each element is addressed in turn in Chapters Two to Five and its role in both writers' constructions of poetic identity in their individual plays is explored and problematised. The conclusion evaluates the radical nature of Cixous' and Tsvetaeva's dramatisations of poetic identity in the context of the representation of the female poet and discusses the evolution of this theme in a chronological approach to their theatre.